2006
DOI: 10.1212/01.wnl.0000233923.63869.8c
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular disease among patients from the Indian subcontinent

Abstract: In this study, the authors document the characteristics of South Asian (SA) cerebrovascular patients. A retrospective medical record review comparing SA (n = 99) and European-American (n = 106) patients was performed. SA patients were younger and had a greater prevalence of diabetes, but lower prevalences of hyperlipidemia and tobacco use. SA patients experienced a 75% lower risk of cardiogenic infarctions, but a threefold increased risk of intracranial atherothrombosis. Risk factor modifications and secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Hence, not only is diabetes more common among South Asians compared to other ethnic groups 33 but also it is likely that this is a hereditable risk factor in this population. 34 In the current study, Ͼ40% of the South Asian stroke survivors had evidence of diabetes, and …”
Section: Discussionmentioning
confidence: 50%
“…Hence, not only is diabetes more common among South Asians compared to other ethnic groups 33 but also it is likely that this is a hereditable risk factor in this population. 34 In the current study, Ͼ40% of the South Asian stroke survivors had evidence of diabetes, and …”
Section: Discussionmentioning
confidence: 50%
“…Hence, not only is diabetes more common among South Asians compared with other ethnic groups, 77 but it is likely that this is a hereditable risk factor in this population. 78 Diabetes among South Asian patients with stroke explains poorer survival in this group 38 and a greater incidence of CVD outcomes among South Asian patients with hypertension. 65 Although the presence of diabetes calls for more stringent management of blood pressure, the underlying pathophysiology that accelerates the risk of stroke is not clear.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…ICS is the most common vascular lesion in Asians with ischemic stroke 2, 3, 4. The estimated prevalence of middle cerebral artery stenosis among asymptomatic Asian patients ranges from 7.2% to 29.6%, while Asian patients with ischemic stroke have a higher ICS incidence of 33% to 84% 4, 19.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the correlation of ICS and ischemic stroke is more prominent in Asians; in contrast, extracranial carotid stenosis (ECS) is more prevalent in whites 1, 2, 3. ICS is thought to be the cause of 33% to 84% of ischemic strokes in Asian populations4 and 8% to 10% of strokes in North America 5, 6.…”
Section: Introductionmentioning
confidence: 99%